Household-level sanitation in Ethiopia and its influencing factors: a systematic review - Novotný, Josef; Mamo, Biruk Getachew (BMC public health, 2022)
BACKGROUND: Within the past two decades, Ethiopia has achieved one of the fastest reductions of open defecation worldwide. This change can be attributed to the implementation of a national sanitation strategy that focused on facilitating community demand for latrine adoption and use of basic self-constructed latrines but less on other preconditions of hygienic sanitation. Recognition of sanitation by policymakers also catalyzed primary research in this area. As such, the synthesis of the available evidence is both warranted and possible. In this article, we thus decided to assess available primary evidence on the household-level sanitation in Ethiopia and its influencing factors. METHODS: We searched primary studies that present findings on the role of factors influencing household-level sanitation outcomes in Ethiopia. We typologically classified sanitation outcomes analyzed in identified literature and computed pooled estimates for the most prevalent ones (measures of latrine availability and use). We characterized thematic types (themes and sub-themes) of influential sanitation drivers and used network analysis to examine the relational patterns between sanitation outcomes and their influencing factors. FINDINGS: We identified 37 studies that met our inclusion criteria-all but one published after 2009. The general latrine coverage pooled across 23 studies was 70% (95% CI: 62-77%), the share of improved latrines pooled across 15 studies was 55% (95% CI: 41-68%), and latrine use pooled across 22 studies was 72% (95% CI: 64-79%). Between-study heterogeneity was high, and no time trends were identified. The identified sanitation outcomes were classified into eight types and factors reported to influence these outcomes were classified into 11 broader themes and 43 more specific sub-themes. Factors around the quality of latrines represented the most frequent sub-theme of consequential drivers. We found that the available research focused predominantly on outcomes concerning the initial adoption and use of basic latrines, emulating the main focus of national sanitation strategy. By contrast, research on drivers of the sustainability of sanitation change and, in particular, on the upgrading of latrines, has been rare despite its urgency. There is a high need to redirect the focus of sanitation research in Ethiopia towards understanding these factors on both the demand and supply side.
Keywords: Ethiopia; Latrine adoption; Etiopie; toalety; Rural Population; venkovské obyvatelstvo; Hygiene; Systematic review; hygiena; Family Characteristics; Humans; Toilet Facilities; Environmental health; lidé; sanitace; charakteristiky rodiny; Sanitation